EFEKTIVITAS EKSTRAK AIR BATANG CIPLUKAN (Physalis minima L.) TERHADAP KADAR MALONDIALDEHID TULANG MANDIBULA TIKUS PUTIH (Rattus norvegicus) Strain Wistar Pasca Ovariectomy - Fadhilah, Nadia; Permatasari, Nur; Widodorini, Trining (Fakultas Kedokteran Gigi UB, 2025)
Estrogen has function as an antioxidant that can reduce free radicals. Hipoestrogen condition will increase oxidative stress in the body. Periodontitis is one of the diseases associated with oxidative stress. Oxidative stress, characterized by increased levels of malondialdehid (MDA). Malondialdehid is usually used to assess the oxidative stress. Phytoestrogens are plant components that have biological activity of estrogen. Ciplukan is a natural ingredient or plant suspected to be a phytoestrogen compound. The theoretical study results showed that ciplukan stem contained physalin, which have a similar effect to estrogen. The purpose of this study is to determine the effectiveness of ciplukan stem extract on malondialdehyde levels in the rat mandibular bone post ovariectomy. Twenty four rats were randomly divided into 6 groups with each 4 rats, that are 3 control groups and 3 groups treated rats that were given the ciplukan stem extract at the end of the first 5 weeks ovariectomy with three different doses: 500 mg/kg BW (K4), 1.500 mg/kg BW (K5), and 2.500 mg/kg BW (K6) for 4 weeks. MDA levels calculated by thiobarbituric acid (TBA) test and read by a spectrophotometer and MDA standard curve created. The results showed the incease of MDA levels can be inhibited at the dose of 500 mg / kg, while at the dose of 1500 mg/kg BW and 2500 mg/kg BW can restore MDA levels similar to normal. There is a strong correlation between the negative direction doses of ciplukan stem extract with MDA levels in mandibular bone (r = -0.507). The conclusion of this study is the ciplukan stem extract can reduce MDA levels in mandibular bone strain of wistar rats after ovariectomy.